Succesful treatment with oral zinc sulphate of widespread plantar warts in a patient under systemic corticosteroid therapy. - Gürkan, A.; Özlü, S.G. (European Journal of Pediatric Dermatology, 2015)
Warts are papillomas caused by the Human Papilloma Virus. Although they can spontaneously resolve, most patients request treatment due to cosmetic concerns or functional impairment. Current treatment options are usually destructive and painful. Zinc is a micronutrient involved in immunologic processes and oral zinc sulphate was reported to be effective in the treatment of warts. Here we report a 13 year-old girl who had widespread viral warts on both soles. She was receiving systemic corticosteroid therapy for relapse of nephrotic syndrome. Warts were successfully treated with oral zinc sulphate for 3 months without any side effects. Oral zinc sulphate could be a new treatment option for warts unresponsive to conventional treatments.